The fruits of disaggregation: The engineering industry, tariff protection, and the industrial investment cycle in Italy, 1861-1913 - Fenoaltea, Stefano (PSL Quarterly Review, 2020)
All the extant interpretations of united Italy’s early industrial development focus on the long swing in industrial investment evident in the familiar indices of the engineering industry’s aggregate product. Disaggregated production series for that industry have now been compiled. The evidence they incorporate establishes that the long swing that dominates the aggregate was actually in the production of hardware, tied to investment in infrastructure. The production of machinery followed a different path: against the extant literature it shows that tariff hikes were influential, and above all that Italy’s purchases of (domestic and foreign) machinery grew very steadily decade after decade. Industrial investment did not grow faster than before in the 1880s or over the belle époque, it did not follow the long swing at all: the disaggregation of the engineering-industry product series has undercut the empirical premise of sixty years of scholarship. JEL codes: E01, N13, N63